2016
DOI: 10.1039/c6mb00031b
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexes of the agonist, inverse agonist and antagonist bound C5a receptor: insights into pharmacology and signaling

Abstract: The C5a receptor (C5aR) is a pharmacologically important G-protein coupled receptor (GPCR) that interacts with (h)C5a, by recruiting both the "orthosteric" sites (site1 at the N-terminus and site2 at the ECS, extra cellular surface) on C5aR in a two site-binding model. However, the complex pharmacological landscape and the distinguishing chemistry operating either at the "orthosteric" site1 or at the functionally important "orthosteric" site2 of C5aR are still not clear, which greatly limits the understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 85 publications
5
21
0
Order By: Relevance
“…However, the mechanism of such action is still unclear in structural terms. In continuation to our earlier reports 8 , 9 , 13 , the comparison of the h C5a-C5aR, h C5a(A8)-C5aR model structural complexes, including the CT peptide variants of h C5a(A8) presented in the study provide the necessary rationalization important for understanding the observed antagonism and the switching of antagonism to agonism at the “site2” of C5aR. Moreover, the native agonist ( h C5a-C5aR) and the engineered antagonist ( h C5a(A8)-C5aR) bound model complexes, respectively presented in the current study rationalize a large set of point mutation based binding and signaling data 12 , 14 – 20 , by estimating the residue specific energetic contribution toward overall binding in structural terms.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…However, the mechanism of such action is still unclear in structural terms. In continuation to our earlier reports 8 , 9 , 13 , the comparison of the h C5a-C5aR, h C5a(A8)-C5aR model structural complexes, including the CT peptide variants of h C5a(A8) presented in the study provide the necessary rationalization important for understanding the observed antagonism and the switching of antagonism to agonism at the “site2” of C5aR. Moreover, the native agonist ( h C5a-C5aR) and the engineered antagonist ( h C5a(A8)-C5aR) bound model complexes, respectively presented in the current study rationalize a large set of point mutation based binding and signaling data 12 , 14 – 20 , by estimating the residue specific energetic contribution toward overall binding in structural terms.…”
Section: Introductionsupporting
confidence: 88%
“…The topologically unique model of C5aR described earlier 8 , 9 , presented in Fig. 1 illustrates a modestly folded β-hairpin like structure with ~30% residues in ordered β-sheet conformation, as estimated from the in silico folding studies of the predicted extended extracellular loop 2 (ECL2) polypeptide [Ac-Y174-RVVREEYFPPKVL C188 GVDYSHDKR-R198-NH 2 ] 8 .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations